Rational Molecular Design and Synthesis of Highly Thermo‐ and Photostable Near‐Infrared‐Absorbing Heptamethine Cyanine Dyes with the Use of Fluorine Atoms. Issue 35 (22nd July 2016) - Funabiki, Kazumasa; Yagi, Kazutaka; Ueta, Masato; Nakajima, Mitsuru; Horiuchi, Masako; Kubota, Yasuhiro; Mastui, Masaki
Abstract: Highly thermo‐ and photostable, near‐infrared‐absorbing heptamethine cyanine dyes were achieved with the use of fluorine‐containing components. In particular, one prepared heptamethine cyanine dye, bearing a tetrakis(pentafluorophenyl)borate as a counter anion and an N ‐ethyl‐2, 2, 2‐trifluoroacetamido group at the meso position, showed not only a high decomposition temperature ( T dt ), but also very high photostability toward white LED irradiation. Abstract : Fluorine makes it strong ! Highly thermo‐ and photostable, near‐infrared‐absorbing heptamethine cyanine dyes were achieved with the use of fluorine‐containing components, such as tetrakis(pentafluorophenyl)borate as a counter anion and an a N ‐ethyl‐2, 2, 2‐trifluoroacetamido group at the meso position (see figure).